Fluorinated Triazole Foldamers: Folded or Extended Conformational Preferences. Issue 2 (8th February 2021) - Laxio Arenas, José; Xu, Yaochun; Milcent, Thierry; Van Heijenoort, Carine; Giraud, François; Ha‐Duong, Tap; Crousse, Benoit; Ongeri, Sandrine
Abstract: Fluorinated peptidomimetic foldamers are still in their infancy. We report here the easy access to fluorinated triazolamers based on 2‐amino‐3, 3, 3‐trifluoropropyl‐1, 4‐triazolyl acetic acid (CF3 −1, 4‐Tz) and on aminomethyl‐1, 4‐triazolyl‐difluoroacetic acid (1, 4‐Tz−CF2 ). Both CF3 −1, 4‐Tz and 1, 4‐Tz−CF2 amino acids were efficiently prepared by copper(I)‐catalyzed Huisgen 1, 3‐dipolar cycloaddition. Their conformational preferences were studied by 2D NMR analyses and molecular dynamic simulations. Foldamers based on CF3 −1, 4‐Tz amino acids are capable of adopting short multi‐stranded β‐sheet‐like structures that are maintained by electrostatic interactions between the triazole proton and N2 atom of neighboring subunits. On the contrary, foldamers based on 1, 4‐Tz−CF2 units adopt elongated β‐strand‐like structures, stabilized by electrostatic interaction between fluorine atoms and their neighboring protons. Abstract : A new twist : The syntheses and the conformational analyses of fluorinated oligomers of triazole, also called triazolamers, are reported. Triazolamers based on trifluoromethyl homo‐1, 4‐Tz amino acid, considered as a mimic of a β, α‐dipeptide, adopt short multi‐stranded β‐sheet‐like structure, while triazolamers based on N ‐difluoromethyl 1, 4‐Tz amino acid, considered as an analogue of Gly‐difluoroGly dipeptide, show elongated β‐strand like structures.